Prokaryotic Expression of H1N1 Influenza A Virus Haemagglutinin Protein Globular Domain (HA1) - Bahreinian, Maedeh; Behzadian, Farida; Fotouhi, Fatemeh (Archives of Medical Laboratory Sciences, 2019)
Background: Influenza viruses are a significant cause of morbidity and mortality. The influenza virus pandemics, 1918, 1977, and especially the most recent one, A/H1N1/2009, made evident the need for generating recombinant Influenza H1N1 antigens which are essential to develop both basic and applied research programs. Among influenza virus proteins, haemagglutinin (HA) is a major surface antigen of influenza virus, thus it is highly topical in influenza research and vaccine engineering programs. Alternatively, expression of fragments of the HA (HA1 and HA2) proteins in prokaryotic systems can potentially be the most efficacious strategy for manufacture of large quantities of influenza vaccine in a short period of time. Materials and Methods: The gene encoding the HA1 protein of the influenza A/Puerto Rico/8/34 was amplified by PCR, then cloned into pTZ57R/T cloning vector. The fidelity of the HA1 open reading frame was confirmed by bidirectional sequencing, then sub-cloned into pET28a prokaryotic expression plasmid, and proteins containing HA1 N-terminally fused to His-Tag were produced in Escherichia coli BL21 through IPTG inducing. The accuracy of the expression was confirmed by running time coursed fraction samples taken before and after the IPTG induction in SDS-PAGE, Western blot analysis were also used for confirmation of the recombinant protein. Results and Conclusion: The HA1 protein produced here could be considered and evaluated as a protective antigen, which its immunogenicity potential needs to be assessed in animal models along with proper control groups. Moreover, it could be subjected for polyclonal antibody preparation, which, in turn, may be used as an essential material in western blot analyses, as well as in other immunological applications, such as ELISA, immunocytochemistry, immunohistochemistry, and other immunological and serological studies.